Indigenous Knowledge and Herbal Medicine: Exploring the Ethnobotany of the Karo Tiganderket Tribe in Indonesia - Singarimbun, Emalia; Elfrida, Elfrida; Indriaty, Indriaty (Heca Sentra Analitika, 2024)
This ethnobotanical study investigates the traditional use of medicinal plants in Tiganderket Village, Karo Regency, Indonesia, to document local plants' diversity, uses, and preparation methods for medicinal purposes. Utilizing a quantitative descriptive approach, data were gathered from 30 informants, including traditional healers and residents. The study identified 92 plant species from 44 families, with the Zingiberaceae family being the most dominant. Frequently used plants, such as Piper betle (belo) and Zingiber officinale (ginger), were primarily employed to treat common ailments like fever, boils, and joint pain. Boiling (74%) was the most common method of plant preparation, and leaves (50%) were the most frequently used plant parts. The Relative Frequency of Citation (RFC) revealed Acorus calamus and Curcuma longa as the most cited species. At the same time, 40 of 66 recorded diseases showed high Informant Consensus Factor (ICF) values, reflecting shared knowledge of plant use. This study highlights the rich preservation of traditional medicinal plant knowledge in Tiganderket Village, which continues to play a crucial role in local healthcare practices.